ON THE AGE OF THE AKDZHAR BEDS AND THE CRETACEOUS-PALEOGENE BOUNDARY IN SOUTHWESTERN TADZHIKISTAN - Viskova L.A.; Oleynik V.V. (My University, 1990)
Our study of bryozoans has enabled us to date the Cretaceous-Paleogene boundary deposits more reliably. Of particularly great interest are the bryozoans from two sections far apart, where they occur in mass quantity: in Borehole 7 of the Beshtentyak gas-condensate and oil deposit and in a natural outcrop in the Koykitau Range. Along with these bryozoan genera, which are not known in deposits younger than Maastrichtian, we found a whole group of genera that also occur in the bryozoan limestones of the Akdzhar beds: Entalophora, Spiropora, Idmonea, Heteropora, Cavrinella, Cyrtopora, Desmepora, Hemicellaria, Pleuronea, Reteporidea, etc. Most of them migrated into the Danian basins from the Cretaceous seas and later died down markedly, all the way to their complete extinction in various epochs of the Paleogene and Neogene. But such genera as Cavarinella, Desmepora, Cyrtopora and Hemicellaria had already become extinct in the Danian. On the other hand, some species of Reteporidea and the Genus Pleuromea did not appear until the Danian.
Keywords: Paleogene; Cretaceous; Кайнозой::Палеоген; Mesozoic::Cretaceous; Cenozoic::Paleogene; Мезозой::Меловая